Fibers in pediatric functional gastrointestinal disorders. Practical considerations from clinical cases. (3rd June 2021) - Romano, Claudio; Pallio, Socrate; Cucinotta, Ugo; Accorsi, Paola; Dipasquale, Valeria
ABSTRACT: Introduction : Functional gastrointestinal disorders (FGIDs) are common in children and incur high direct and indirect social costs. Partially hydrolyzed guar gum (PHGG) is a natural and water-soluble dietary fiber that is derived from guar gum. It has been proposed as complementary therapy in pediatric FGIDs, especially in chronic functional constipation and irritable bowel syndrome. Areas covered : By focusing on four clinical cases, this article illustrates the use of PHGG fiber as sole supplement ingredient or as a formula component in orally- and tube-fed children suffering from malnutrition due to FGIDs, with or without special medical conditions such as neurological disability. The formula used was a whey peptide-based nutritionally complete formula containing PHGG as a source of soluble dietary fiber. It was offered under medical supervision and after full consideration of all feeding options. Expert opinion : Implementing appropriate feeding behaviors, adapted to age and potential comorbidities, is an essential requisite for therapeutic management of FGIDs. The use of a PHGG supplement or a nutritionally complete formula containing PHGG as a source of soluble dietary fiber can be helpful to manage pediatric FGIDs.